135k views
3 votes
What is the average rate of change (ARC) from x = -3 to x = -2?A.2B.-2C.-1D.4

What is the average rate of change (ARC) from x = -3 to x = -2?A.2B.-2C.-1D.4-example-1

1 Answer

1 vote

Step 1: Let's recall the formula for the Average Rate of Change:

ARC = (f (b) - f(a)=/b - a

Step 2: According to the graph provided, we have:

f (-3) = 0

f (-2) = 2

Step 3: Replace the values we know in the formula:

ARC = 2 - 0/-2 - (-3)

ARC = 2 /-2 + 3

ARC = 2/1

ARC = 2

Now you can decide which of the alternatives given is the correct

User Jonasb
by
6.4k points